The results of the search and study of young stellar objects with Ha emission in the Byurakan Observatory - Nikoghosyan, E. H.
One of the main observational properties of young stellar objects in the optical range is the presence of emission lines, in particular H (6563 Å). Therefore, detection of H emission is the most common spectroscopic means for identification of young stars. The paper presents the results of searching and studying of young stellar objects in several star forming regions carried out on the 2.6 m telescope in Byurakan observatory. The quantitative relationships between objects with different stage of activity are considered. In addition, a statistical analysis of H activity and other manifestations of PMS activity (X-ray, IR excess), as well as an evolutionary age of the H emitters in several star-forming regions is provided.
Keywords: Astronomy